METHODOLOGICAL PRINCIPLES FOR EVALUATION OF EFFICIENCY OF THE PUBLIC SECTOR - Smolii , L.V. (The actual problems of regional economy development, 2020)
The purpose of the article is to substantiate approaches to understanding the nature and methodological principles of assessing the effectiveness of the public sector of the national economy. The study is based on methods of systematic and logical analysis, which revealed a variety of views on the problem of public sector efficiency. The application of the system method made it possible to investigate the conceptual relationship between the main components of the public sector; the use of methods of dialectics, scientific abstraction, institutional approach allowed to reveal the essence and structure of the social sector of the economy; methods of analysis and synthesis were used in the formation of an improved list of indicators of public sector efficiency. The main approaches to understanding the category of "public sector" are highlighted, its structure is identified. The need to reconsider the role of "third" sector institutions in the public sector is substantiated. The main concepts of evaluating the efficiency of the public sector of the economy are considered. The main problems that hinder the objective analysis of the efficiency of the public sector in general and its structural components in particular are identified. The existing methods of assessing the effectiveness of the public sector are analyzed, their shortcomings are outlined, and the list of indicators that form such an assessment is expanded. The scientific novelty of the obtained results is to improve the parameters of assessing the effectiveness of the public sector, which, in contrast to the application of existing methods, provides a more complete picture of the results of institutions of the "third" sector in cooperation with public and municipal subsectors. The practical significance of the study is that the use of improved methods for assessing the effectiveness of the public sector will identify timely areas for modernization of social development strategies and improve the level and quality of life of citizens.